Improving Human Resources in The Package C Equality Program Through Digital Skill Training at PKBM Permata Bangsa Surabaya - Raheny, Ifa Budi; Atmadja J.A, I Ketut; Nugroho, Rivo (Universitas Negeri Padang, 2024)
This research aims to explore how the Digital Skills Training Program at PKBM Permata Bangsa Surabaya improves the digital skills of Package C Equality Program students. The research method used is a qualitative approach, with data collection techniques including participatory observation, in-depth interviews, and document analysis. The research results showed that out of a total of 100 training participants, 70% succeeded in obtaining a certificate after attending training regularly, while the remaining 30% were unable to participate in training consistently. The training material presented includes Problems and Innovation, Digital Literacy, Content Creation, Social Media, Digital Marketing, and Web Application Creation. However, there are still obstacles to participation, especially those related to busy work and a lack of support from participants' parents. However, the participants' enthusiasm after the training remained high, especially in applying the skills they learned. Thus, this research provides valuable insight intothe role of digital skills training in improving human resources in the digital era. Keyword: Pelatihan Digital Skill, Program Kesetaraan, PKBM Permata Bangsa, Keterampilan Digital, Pendidikan Non-Formal